Recent Advances in Parallel Virtual Machine and Message Passing Interface 16th European PVM/MPI Users' Group Meeting, Espoo, Finland, September 7-10, 2009, Proceedings - Ropo, Matti; Westerholm, Jan; Dongarra, Jack (Programming and Software Engineering, 2009)
This book constitutes the refereed proceedings of the 16th European PVM/MPI Users' Group Meeting on Recent Advances in Parallel Virtual Machine and Message Passing Interface, EuroPVM/MPI 2009, held in Espoo, Finland, September 7-10, 2009. The 27 papers presented were carefully reviewed and selected from 48 submissions. The volume also includes 6 invited talks, one tutorial, 5 poster abstracts and 4 papers from the special session on current trends in numerical simulation for parallel engineering environments. The main topics of the meeting were Message Passing Interface (MPI)performance issues in very large systems, MPI program verification and MPI on multi-core architectures.